Crisis and Continuity. Land and Town in the Late Medieval Castile - Nogueira, Carlos Roberto F. (Revista de História, 1997)
RUIZ, Teofilo F. Crisis and Continuity. Land and Town in the Late Medieval Castile. Philadelphia, University of Pennsylvania Press, 1994.